2018
DOI: 10.1590/2175-623684865
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação e Gestão da Educação Infantil em Municípios Brasileiros

Abstract: Resumo: Estudos que elucidam como os temas avaliação e gestão da educação infantil vêm sendo tratados na literatura nacional evidenciam serem ainda escassas pesquisas que analisem propostas direcionadas à avaliação deste segmento da educação básica e, tampouco, à interface entre esse tema e a gestão educacional. Essa constatação motivou o estudo que se voltou a identificar produções acadêmicas que tomaram como objetos de investigação os temas gestão e/ou avaliação da educação infantil, cujas contribuições apoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…When mapping proposals of Early Childhood Education evaluation in debate in Brazil, Sousa (2014Sousa ( , 2018 stresses that, beyond a technical discussion, there are impasses concerning the political dimension of evaluation. Also, depending on the result of the dispute around the object of evaluation, there might be repercussions for the organization of SAEB, to which the Early Childhood Education was recently integrated.…”
Section: Pertinent Principles and Issues To Propose Or Analyze An Earlymentioning
confidence: 99%
See 2 more Smart Citations
“…When mapping proposals of Early Childhood Education evaluation in debate in Brazil, Sousa (2014Sousa ( , 2018 stresses that, beyond a technical discussion, there are impasses concerning the political dimension of evaluation. Also, depending on the result of the dispute around the object of evaluation, there might be repercussions for the organization of SAEB, to which the Early Childhood Education was recently integrated.…”
Section: Pertinent Principles and Issues To Propose Or Analyze An Earlymentioning
confidence: 99%
“…The authors underline aspects in most of the initiatives: supplies (material, physical infrastructure) and processes (management, interpersonal relations with students and families, curriculum, among others) of the educational institutions. Based on the analysis of studies addressing municipal evaluations, Sousa and Pimenta (2018) observe that they tend to be restricted to the children's learning, choosing this indicator as an expression of the quality of Early Childhood Education, even though there are registers of cities that comprise in their proposals other aspects, like physical infrastructure, human and material resources, and others. Garcia, Garrido and Marconi (2017) analyzed the infrastructure of Early Childhood Education schools and concluded that this dimension is accountable for the legitimation of social inequalities.…”
Section: Relevant Dimensions and Indicators For The Proposal Of A Mon...mentioning
confidence: 99%
See 1 more Smart Citation
“…Estudios realizados por importantes investigadores sobre la educación de niños pequeños en Brasil, como Campos (2020) y Sousa (2014), señalan los impasses en el campo de la AVEI y la necesidad de apropiación de estas discusiones por parte de los profesionales interesados en la educación de los niños brasileños. Esta advertencia es aún más contundente en la actualidad, ya que, en 2019, la EI comenzó a integrar el Sistema de Evaluación de la Educación Básica (SAEB) (Mec, 2020).…”
Section: Introductionunclassified